Pharmacokinetic and pharmacodynamic evaluation of ramelteon: an insomnia therapy. (July 2015) - Spadoni, Gilberto; Bedini, Annalida; Lucarini, Simone; Mor, Marco; Rivara, Silvia
<x xml:space="preserve">Abstract</x> Introduction: <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Ramelteon&logicalOpe1=OR&field2=articletitle&text2=Ramelteon&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Ramelteon, a selective melatonin receptor agonist, is the first member of a novel class of hypnotics. It is approved for the treatment of insomnia characterized by sleep onset difficulties in the US and Japan, but not in Europe. Areas covered: The main clinical properties as well as safety issues of ramelteon are described. Relevant publications reporting ramelteon characteristics and its use in insomnia disorder were identified using PubMed and SciFinder databases up to January 2015. Additional information was collected from the US clinical trials database and from Takeda website. Expert opinion: Despite its high prevalence and economic burden, insomnia disorder remains mostly untreated. Ramelteon has demonstrated sleep-promoting effects in clinical trials and clinical practice, and it is not associated with the adverse effects typical of other class of hypnotics. Its efficacy appears to be relatively modest compared to current insomnia therapeutics, and its use seems restricted to patients with sleep onset difficulties. Assessment of ramelteon effects on sleep quality and maintenance, daytime function and of improvements in comorbid insomnia conditions deserves further studies. The potential application of ramelteon in other pathological conditions could open the way to novel therapeutic approaches as well as to new market opportunities.